PENINGKATAN MUTU KAKAO MELALUI FERMENTASI MENGGUNAKAN STARTER KERING BAKTERI ASAM LAKTAT DAN BAKTERI ASAM ASETAT INDIGENUS KAKAO ACEH - yusya abubakar; Murna Muzaifa; Heru Prono Widayat; Martunis Martunis (AGROINTEK, 2022)
Indonesia is one of the cocoa producing countries in the world. Although the amount of cocoa production and planted area has increased, the quality of cocoa beans in Indonesia including Aceh is still low. This happened because the farmers did not carry out the fermentation process. Fermentation is one of the most important steps that must be taken to improve cocoa quality. However, it is rarely done because it takes a long time. The purpose of this study was to analyze the use of starter bacteria lactic acid (LAB) and acetic acid (BAA) indigenous Aceh cocoa in fermenting Aceh cocoa. The research was conducted by fermenting cocoa with two different factors, namely the type of starter (control, LAB, BAA, LAB-BAA mixture) and fermentation time (3,4 and 5 days). The results showed that the use of Acehnese cocoa indigenus bacteria starter and different fermentation time had an effect on fermentation conditions and the quality of fermented cocoa beans. Fermentation of cocoa beans with the addition of a dry starter affects the pH value and the percentage of fermented cocoa beans. The best treatment was obtained when using LAB starter with fermentation time of 4 days, with the same fermented quality of cocoa beans with fermentation using LAB and BAA for 5 days of fermentation. Further research is needed to confirm the quality of fermented cocoa beans produced by analyzing volatile chemical components and flavors.